IMPLEMENTASI MODEL INKUIRI TERBIMBING BERBASIS PERFORMANCE ASSESSMENT PADA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK SMA - Iftirani, Fifta Itsna; Sunarti, Titin (IPF: Inovasi Pendidikan Fisika, 2024)
Critical thinking skills are 21st century skills that must be mastered by students. This study aims to describe the implementation, improvement of critical thinking skills, and students' responses after applying the guided inquiry learning model based on performance assessment. This type of research is Descriptive-Quantitative using the Pre-Experimental method. This research design uses One Group Pretest-Postest Design consisting of three classes, namely one experimental class and two replication classes. Before the learning is done, students are given an initial ability test (pretest) and at the end of the learning is given a final ability test (posttest). The research instruments used were learning implementation observation sheet, critical thinking skills test sheet, performance assessment sheet, and response questionnaire sheet. The data analysis techniques used were learning implementation analysis, paired t-test, n-gain calculation, ANOVA, and response questionnaire analysis. The results of data analysis show that the implementation of learning has been carried out very well as evidenced by the results of the average percentage obtained of 100%, there is a significant difference between the pretest and posttest scores, and there is an increase as evidenced by the average n-gain in the three classes successively of 0.74; 0.77; 0.78 with a high category, and the increase occurs consistently in the three classes, the average percentage of student responses in the three classes successively of 85.4%; 85.7%; 79 with a very good category. It can be concluded that the implementation of learning with the guided inquiry learning model based on performance assessment has been carried out very well, students' critical thinking skills have increased after learning with the guided inquiry model based on performance assessment, and the three classes received very good learning and positive responses. Keywords: Guided inquiry, Performance Assessment, Critical Thinking Skills